The Effect Of Competence and Facilities On Teacher’s Performance At Haji Masri Darul Ilmi Murni Islamic Educational Foundation, Namorambe District, Deli Serdang Regency - Ega Siddik; Abd Rasyid Syamsuri; Julianto Hutasuhut; Mutawaqil Bilah Tumanggor (International Journal of Science, Technology & Management, 2021)
This study aims to analyze the effect of competence and facilities have a positive and significant effect on teacher’s performance at Haji Masri Darul Ilmi Murni Islamic Educational Foundation, Namorambe District, Deli Serdang Regency. The method used in this study is a quantitative method with several tests, that are the classical assumption test and multiple linear regression. Based on the results of the study, it can be seen that competence (X1) has a t-count value of 3.263 and a t-table of 1.663 when compared to t-count, the results are 3.263> 1.663, so it can be concluded that competence has a positive and significant effect on teacher performance (Y). The facility (X2) has a t-count of 5.595 when compared to the t table, the result is 5.595>1.663, so it can be concluded that the facilities have a positive and significant effect on teacher’s performance (Y). Simultaneously, competence and facilities have a positive and significant influence on teacher’s performance. This means that the hypothesis in this study is accepted, proved by the calculated F value > F table (75.790 > 3.11). The results of the coefficient of determination indicate that competence and facilities have an influence on teacher’s performance by 65.2%, while the remaining 34.8% is influenced by other variables which are not examined in this study.